Lipid-Based Particles: Versatile Delivery Systems for Mucosal Vaccination against Infection - Corthésy, Blaise; Bioley, Gilles (Frontiers in Immunology, 2018)
Vaccination is the process of administering immunogenic formulations in order to induce or harness antigen-specific antibody and T cell responses in order to protect against infections. Important successes have been obtained in protecting individuals against many deleterious pathological situations after parenteral vaccination. However, one of the major limitations of the current vaccination strategies is the administration route that may not be optimal for the induction of immunity at the site of pathogen entry, i.e. mucosal surfaces. It is now well documented that immune responses along the genital, respiratory or gastrointestinal tracts have to be elicited locally to ensure efficient trafficking of effector and memory B and T cells to mucosal tissues. Moreover, needle-free mucosal delivery of vaccines is advantageous in terms of safety, compliance and ease of administration. However, the quest for mucosal vaccines is challenging due to: (1) the fact that antigen sampling has to be performed across the epithelium through a relatively limited number of portals of entry; (2) the deleterious acidic and proteolytic environment of the mucosae that affect the stability, integrity and retention time of the applied antigens; (3) the tolerogenic environment of mucosae, which requires the addition of adjuvants to elicit efficient effector immune responses. Until now, only few mucosally applicable vaccine formulations have been developed and successfully tested. In animal models and clinical trials, the use of lipidic structures such as liposomes, virosomes, immune stimulating complexes, gas-filled microbubbles and emulsions has proven efficient for the mucosal delivery of associated antigens and the induction of local and systemic immune reponses. Such particles are suitable for mucosal delivery because they protect the associated payload from degradation and deliver concentrated amounts of antigens via specialized sampling cells (microfold cells) within the mucosal epithelium to underlying antigen-presenting cells. The review aims at summarizing recent development in the field of mucosal vaccination using lipid-based particles. The modularity ensured by tailoring the lipidic design and content of particles, and their known safety as already established in humans, make the continuying appraisal of these vaccine candidates a promising development in the field of targeted mucosal vaccination.